FILSAFAT ORDINARY LANGUAGE DAN PEMBELAJARAN BAHASA - NURLAILA NURLAILA (Ta'dib, 2014)
Ordinary language philosophy was one of the streams of analical language philosophies that had layed on how language was used. This became basic principle in studying pragmatic in lingusitic study. The idea of ordinary language about the pragmatic approach in learning language oriented to create the students’ communication ability that was appropriate with the context where the communication happened. It was because learning language means leaning communication and language as a tool of communication that could be used in various function and situation. Kata kunci: filsafat, ordinary language, pragmatik, bahasa, pembelajaran